1973
DOI: 10.1021/ja00797a004
|View full text |Cite
|
Sign up to set email alerts
|

Excited states of skin-sensitizing coumarins and psoralens. Spectroscopic studies

Abstract: Several skin-sensitizing psoralens and their model coumarins fluoresce weakly and phosphoresce relatively strongly. The excited states of some of these molecules have been investigated in rigid matrices at 12 and 77 °K by means of luminescence and photoselection measurements. Coumarins and psoralens exhibit a relatively high phosphorescence to fluorescence ratio ( / > 1); however, in coumarylpyrone (benzo[l,2-6:4,5-6']dipyran-2,8-dione) and coumarins with strong charge transfer substituents, the ratio is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
154
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(181 citation statements)
references
References 1 publication
27
154
0
Order By: Relevance
“…The spin density at the C=C group of the pyrone in the coumarin triplet is about 0.5, which is lower than the M O values calculated by Song and Gordon [132] but still in good agreement. The location of TI (n, a*) and S, (n, n*) with its nearby (n, n*) is in good agreement with Mantulin and Song [86].…”
Section: Cournurinssupporting
confidence: 68%
“…The spin density at the C=C group of the pyrone in the coumarin triplet is about 0.5, which is lower than the M O values calculated by Song and Gordon [132] but still in good agreement. The location of TI (n, a*) and S, (n, n*) with its nearby (n, n*) is in good agreement with Mantulin and Song [86].…”
Section: Cournurinssupporting
confidence: 68%
“…Although coumarin itself provides a fairly low fluorescence quantum yield at room temperature in most organic solvents (Song and Gordon, 1970;Lakowicz, 1999), the presence of different electron withdrawing or accepting substituents on the coumarin core structure can greatly influence the fluorescence properties (Mantulin and Song, 1973;de Melo et al, 1994;Reichardt, 1994;Gao et al, 2000;de Melo and Fernandes, 2001;Ammar et al, 2003;Sharma et al, 2003). The nature and position of substituents is important for the fluorescence behaviour of these compounds, and many spectroscopic and theoretical studies have been undertaken to characterize the photophysical behaviour of these substances (Machado et al, 2001(Machado et al, , 2003Ionescu and Hillebrand, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Psoralen, a naturally occurring coumarin derivative had been successfully used for clinical treatment of dermatological disorders (Mantulin and Song, 1973). It has been shown that psoralen can photoreact with unsaturated lipids and with molecular oxygen to produce active oxygen species such as superoxide and singlet oxygen that can cause damage to cell membrane (Park et al, 1996).…”
Section: Discussionmentioning
confidence: 99%